2009
DOI: 10.1080/10236660903031025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(o-toluidine) in DMF/Water Mixture Using Benzoyl Peroxide

Abstract: The chemical polymerization of o-toluidine was carried out in dimethylformamide=aqueous HCl solution using benzoyl peroxide. The conductivity of poly(o-toluidine) (POT) doped with HCl changed from 2.0 Â 10 À4 to 15.6 Â 10 À4 S cm À1 depending on the polymerization parameters. The solubility of POT in DMSO was found as 0.3 g=100 mL, in which the solubility of HCl-doped polyaniline was 0.042 g=100 mL. Characterization of synthesized POT was performed by conductivity, solubility, FT-IR, UV-vis, and TGA techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Pbp polymerize stepwise into the macromolecules and thus the degree of polymerization increases steadily. Deviating from the reaction conditions, either an unselective reaction occurred, or the conversion was too low [ 7 , 17 , 18 , 19 , 20 , 21 , 22 ]. The results of this study show good agreement with the previous studies reported for other similar conducting polymers [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pbp polymerize stepwise into the macromolecules and thus the degree of polymerization increases steadily. Deviating from the reaction conditions, either an unselective reaction occurred, or the conversion was too low [ 7 , 17 , 18 , 19 , 20 , 21 , 22 ]. The results of this study show good agreement with the previous studies reported for other similar conducting polymers [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to prepare and manufacture conductive polymers began in the 1970s, and many studies have been conducted in this subject [1]. Polyaniline is one of the leading members of the conductive polymer family [2], has gained broad attention due to its distinctive properties and characteristics such as high electrical conductivity and environmentally stable, reversible proton doping and simple synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline is one of the leading members of the conductive polymer family [2], has gained broad attention due to its distinctive properties and characteristics such as high electrical conductivity and environmentally stable, reversible proton doping and simple synthesis. [1]. Due to their growing application in several areas, such as batteries [3], chemical detectors [4], light-emitting diodes [5], etc., these notable characteristics of polymers have drawn significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Both UVvis and FTIR results reveal that the POT nanostructure is that of a typical doped polymer in its emeraldine salt form. 21,22 3.2.2 X-ray of NPOT Figure 3 shows the X-ray diffraction (XRD) patterns of NPOT, and the X-ray profile shows three well-defined peaks for the POT prepared. The peaks are observed at 2θ ¼ 15 deg, 20 deg, and 25 deg.…”
Section: Ftir Spectroscopy Of Potmentioning
confidence: 99%